DNA metabarcoding uncovers dispersal-constrained arthropods in a highly fragmented restoration setting - Peter Contos; Heloise Gibb; S Jellinek; Nicholas Murphy (2023)
Degraded areas are often restored through active revegetation; however, recolonization by animals is rarely engineered. Recolonization may be rapid for species with strong dispersal abilities. However, poor dispersers, such as many flightless arthropods, may struggle to recolonize newly restored sites. Actively reintroducing or “rewilding” arthropods may therefore be necessary to facilitate recolonization and restoration of arthropod communities and the ecological functions they perform. However, active interventions are rare. The purpose of this study was twofold. First, we asked whether potential source remnant arthropod communities were dispersal-constrained and struggling to recolonize restoration sites. Second, we tested whether reintroducing entire arthropod communities from remnant populations would help dispersal-constrained species establish during farmland ecological restoration in southern Australia. Rewilding was conducted in summer 2018 by transplanting leaf litter, soil, and entire communities contained within it from remnant source populations into geographically isolated restoration sites, which were paired with untreated controls (n = 6 remnant, rewilding transplant, and control sites). We collected leaf litter and extracted arthropod communities 19 months after the initial rewilding event, then sequenced mite, springtail, and insect communities using a metabarcoding approach. Within all groups, community similarity decreased with spatial distance between sites, suggesting significant dispersal barriers. However, only mite communities showed a strong response to rewilding, which was expressed as increased compositional similarity toward remnant sites and greater species richness relative to controls. Our results demonstrate that many arthropod species may struggle to recolonize geographically isolated restoration sites and that full community restoration requires active interventions via rewilding.